Exogenous l-Valine Promotes Phagocytosis to Kill Multidrug-Resistant Bacterial Pathogens - Chen, Xin-hai; Liu, Shi-rao; Peng, Bo; Li, Dan; Cheng, Zhi-xue; Zhu, Jia-xin; Zhang, Song; Peng, Yu-ming; Li, Hui; Zhang, Tian-tuo; Peng, Xuan-xian (Frontiers in Immunology, 2017)
The emergence of multidrug-resistant bacteria presents a severe threat to public health and causes extensive losses in livestock husbandry and aquaculture. Effective strategies to control such infections are highly demanded. Enhancing host immunity is an ideal strategy with less side-effects than antibiotics. To explore any metabolite candidates, we applied metabolomic approach to investigate the metabolic profiles of mice after Klebsiella pneumoniae infection. Compared to the mice comprised to K. pneumoniae infection, the mice survived from the infection displayed an elevated level of L-valine. Our further analysis showed that L-valine increased phagocytosis of macrophages, thereby reducing the load of pathogens not limited to K. pneumoniae but also E. coli clinical isolates in infected tissues. Two mechanisms are involved: L-valine activates the PI3K/Akt1, and promotes NO production through inhibition of arginase activity. The NO precursor, L-arginine, is necessary for the phagocytosis of L-valine-stimulated macrophages. Valine-arginine combination therapy has a stronger ability in killing K. pneumoniae and presents the similar effect in other Gram-negative bacteria (E. coli, Pseudomonas aeruginosa) and Gram-positive bacterium (Staphylococcus aureus). Our study extends the role of metabolism in innate immunity and develops the possibility of employing the metabolic modulator-mediated innate immunity as a therapy for bacterial infections.